The Effect Of Substrate Temperature And Annealing On The Photoresponse Of Zno Uv Sensor - Ahmad, Halim (2013)
Zinc Oxide (ZnO) is a II-VI compound semiconductor with a direct band gap of 3.37 eV and a high exciton binding energy of 60 meV. Thus, ZnO based optoelectronic devices working in UV region have been studied extensively. For the wide applications of ZnO, numerous ZnO thin films nanostructure preparations have been successfully attempted. In this work, a coherent effort has been carried out on the synthesis, characterization and device fabrication of ZnO based UV photodetector. All ZnO nanostructures were synthesized by depositing ZnO on SiO2/Si substrates. The results of this work have been divided into three parts. The first part was to characterize the ZnO sample that was deposited at different substrate temperatures and then undergone heat treatment at 900 °C. The findings of this part include improvement of the crystalline and optical quality due to heat treatment-by increasing the deposition temperature (Room Temperature to 200 °C in this experiment) provides atoms with enough activation energy to diffuse into the stable atomic sites in the crystal lattice and impurities to move to grain boundary, resulting in forming large crystallites through cluster coarsening, the demonstration of UV and green emissions showing its intensity was temperature dependence. Significant drop in decay time td in photoresponse was also revealed. The second part was to characterize the ZnO sample deposited to different thickness. The findings of this part include the rise in PL intensity as the thickness increase. The maximum UV illuminated current to leakage current was at the thickness of 1230 nm. This sample also recorded the fastest rise time of 128.5 s. The last part was to characterize the optoelectrical properties of different design of UV Photodetector, which include the double Schottky barrier and MSM UV photodetectors.